Clinical relevance of atypical squamous cells of undetermined significance by the 2001 Bethesda System: Experience from a cervical cancer high incidence region - Kantathavorn N. (2014)
The aim of this study was to evaluate the underlying lesions and factors predicting cervical intraepithelial neoplasia (CIN) 2+ in women who had "atypical squamous cells of undetermined significance" (ASC-US) on cervical cytology in the region with a high incidence of cervical cancer. This study was prospectively conducted at Chiang Mai University Hospital, Chiang Mai, Thailand. All women with ASC-US cytology undergoing colposcopic evaluation between October 2004 and August 2008 were recruited. During the study period, 208 women were enrolled. Mean age was 44.4 years. The histopathologic results at the initial evaluation were as follows: CIN 2-3, 21 (10.1%); adenocarcinoma in situ, 3 (1.4%); cancer, 5 (2.4%); CIN 1, 26 (12.5%); and no lesions, 153 (73.6%). Multivariate analysis revealed that nulliparity (adjusted odds ratio [aOR] =4.09; 95% confidence interval [CI] = 1.04-16.10) and current oral contraceptive use (aOR=2.85; 95%CI= 1.14-7.15) were independent predictors for having CIN 2+ at the initial colposcopy. At the median follow-up time of 6.7 months, CIN 2-3 lesions were additionally detected in 2 women. In conclusion, ASC-US cytology in our population has a relatively high prevalence of underlying invasive carcinoma. Nulliparity and current oral contraceptive use are independent predictors for harboring CIN 2+.